Anava Upaya in the Saivagama Nusantara Text - Suwantana, I Gede; Nerawati, Ni Gusti Ayu Agung; Bintang, Ida Ayu Putu; Wariati, Ni Luh Gede (Journal of Ecohumanism, 2025)
Anava upaya is one of the four teachings of Yoga in Saivagama. This teaching emphasizes the use of body parts as objects of meditation. There are five types of this anava upaya, namely dhyana, ucchara, varna, karana, and sthana kalpana. Dhyana is meditation on the dissolution of the physical elements from the grossest to the subtlest and ends with Siva. Ucchara is a meditation technique using prana as an object. Varna is a meditation technique using the sounds that come out of the in-breath and out-breath. Karana is a technique of using both the gross and the subtle bodies of the cause. Finally, sthana kalpana is a technique with the use of in and out breaths, as well as various objects outside the body as media for meditation such as rituals, pictures and the like. This work descriptively describes the five types of yoga in the Saivagama Nusantara text. All these techniques are used in order to re-realize the True Self that has been hidden by avidya. Through these five types of effort or yoga, sadhakas are expected to be able to achieve moksha, namely the liberation of the atma from the bondage of samsara.